Use of Fairy Tales in the Legal Education of Children Aged 5-8 - Victoriia, Tsypko; Vasylieva, Larysa; Irina, Ershova; Alexander; Yulia, Fedorchuk (International Journal of Psychosocial Rehabilitation, 2020)
The question of using fairy tales in the educational process of children of preschool age is considered. The necessity of realization of this process in close interaction with parents is proved. Effectiveness of plot and roleplaying games and analysis of fairytale plots, didactic games in the process of legal education is shown.1. Legal education must be carried out in close cooperation with the family;2. Effective means of legal education of senior preschool children are fairy tales, story and role-playing games using them, didactic games, problem The results of the legal upbringing of preschool children can be considered as an understanding of children's responsibilities and rights, the ability to assess their own actions and those of others from a legal perspective, and the ability to comply with obligations and prohibitions. The main direction of the legal upbringing of children is the formation of children's duties and rights, their place in society, and this implies:1. Familiarity with the duties and rights of people (in an accessible form, this can be done by reading fairy tales)2. Formation of the basis of moral and legal norms of conduct in society.3. And the use of fairy tales can be useful for all this.